A meso-triphenylamine-BODIPY derivative for the optical chemosensing of metal ions - Gonçalves, Raquel C. R. (2021)
The design and synthesis of organic molecules for recognition of biologically/environmentally important metal ions has emerged as a highly regarded research field. The BODIPY (4,4-difluoro-4-bora-3a,4a-diaza-s-indacene) core is a versatile signaling molecule that can be fine-tuned with functional groups to create selective binding sites to improve its optical proper-ties. As an extension of the work developed in our research group, we report the synthesis and characterization of a BODIPY functionalized with triphenylamino and a formyl group at the meso and 2-position, respectively, for the highly selective detection of Cu2+ and Fe3+. The preliminary study of the BODIPY derivative as optical chemosensor was carried out in acetonitrile solution in the presence of different cations, and interactions with Cu2+ and Fe3+ induced a perceptible color change. UV-visible titrations showed changes in the absorption spectra upon the addition of three equivalents of each cation, with the appearance of a new absorption band at 693 nm.